Qualitative analysis of psychosocial impact of diagnosis of Chlamydia trachomatis: implications for screening. Issue 7280 (27th January 2001) - Duncan, Barbara; Hart, Graham; Scoular, Anne; Bigrigg, Alison
Abstract: Objectives: To investigate the psychosocial impact for women of a diagnosis of Chlamydia trachomatis and discuss the implications for the proposed UK chlamydia screening programme. Design: Qualitative study with semistructured interviews. Interview transcripts analysed to identify recurrent themes. Participants: Seventeen women with a current or recent diagnosis of chlamydia. Setting: A family planning clinic and a genitourinary medicine clinic in Glasgow. Results: Three themes were identified: perceptions of stigma associated with sexually transmitted infection, uncertainty about reproductive health after diagnosis, and anxieties regarding partner's reaction to diagnosis. Most women had not previously perceived sexually transmitted infections as personally relevant; this was a function of stereotypical beliefs about who was "at risk" of sexually transmitted infection. These beliefs were pervasive and negatively affected reactions to diagnosis and produced anxiety about disclosure of the condition to others (particularly sexual partners) and future reproductive morbidity. This anxiety, given the uncertain natural history of chlamydia, may prove difficult to dispel. Conclusions: There are three primary areas of concern for women after a diagnosis of chlamydia which need to be examined in the proposed screening programme. Information provided should normalise and destigmatise chlamydial infection and positively promote genitourinary medicine services. Support services should be available because notification of partner can cause anxiety. Uncertainty about future reproductive morbidity may be inevitable; staff providing screening will require guidance in providing advice under such conditions.